Water-Nutrition-Health Linkage in Rapidly Urbanizing Economies: A Socio-Epidemiological Approach to Unpack the Linkages in Urban India - Saravanan, V.S.; Saiyed, Shahin (2020)
Objectives: To assess the socio-economic, and environmental burden on nutritional status of the members in the city. To examine the strategies adopted by individuals with diverse nutritional status on their health-seeking behaviour.